Geology laboratory manual for distance learning - Ruhle, James L. (Northbrook, Ill Hubbard Press, 2000)
Describes the origin and age of the earth, its composition and physical properties, the forces that change it, and the significance of its fossils.
Keywords: Geology; Geology